PROBLEMS OF TEACHERS, STUDENTS, AND PARENTS IN ONLINE LEARNING DURING PANDEMIC COVID-19 - Jazaul Chusna (Citra Dharma Cindekia, 2022)
The Covid-19 pandemic that hit Indonesia had an impact on all areas of life, including education. The online education system that is currently running poses several problems for educators, students, and parents. The purpose of this study is to reveal more deeply what problems are faced by educators, students, and parents during the online learning process. The research method used is literature study by taking reading sources through textbooks, scientific journals, and other relevant sources. The results of this study indicate that online learning poses various problems for educators, students, and parents. Approximately 11 problems were found during online learning. Generally, these problems occur because of internet network problems and the unpreparedness of teachers, students, and parents in carrying out their roles in the online learning system.